Choose to Fight or Choose to Flee? A Network Embeddedness Perspective of Executive Ship Jumping in Declining Firms - Jiang, Han; Cannella, Albert A.; Xia, Jun; Semadeni, Matthew (Strategic management journal, 2017)
Research summary: Executives in declining firms may engage in ship‐jumping behavior (i.e., voluntarily move to new employers before the failure occurs) to avoid the stigma of failure. However, it is unclear how executives decide whether or not to jump ship. Building on a network embeddedness perspective, we highlight how three network‐based indicators (i.e., executive social capital, the social capital of other peers in the declining firm, and the declining firm's alliance network) influence the executive‐level ship‐jumping decision by shaping its benefits and opportunity costs. Using data from executives at failing firms in China, we find support for our hypothesized relationships. Our research provides important insight into the network mechanisms driving the ship‐jumping decision. Managerial summary: Executives at failing firms have a choice: stay and attempt to rescue the firm from failure or exit and avoid the stigma of the failure (i.e., jump ship). Yet, little is known about what factors affect this choice. We propose that social capital plays an important role in the decision. Our evidence from specially treated (*ST) public firms in China finds that ship jumping is lowest at low and high values of social capital, and highest at moderate levels of social capital (an inverted U‐shaped relationship). In addition, higher levels of peer social capital (in the declining firm) as well as a well‐established firm‐level alliance network discourage the ship‐jumping choice. Copyright © 2017 John Wiley & Sons, Ltd.